Immune Escape by Non-coding RNAs of the Epstein Barr Virus - Münz, Christian (Frontiers in Microbiology, 2021)
Epstein Barr virus (EBV) is one of the most successful pathogens of humans, persistently colonizing more than 95% of the adult human population. At the same time EBV encodes oncogenes that can readily transform human B cells in culture and threaten healthy virus carriers with lymphomagenesis. Cytotoxic lymphocytes have been identified in experimental models and by primary immunodeficiencies as the main protective immune compartments controlling EBV. EBV has reached a stalemate with these cytotoxic T and innate lymphocytes to ensure persistence in most infected humans. Recent evidence suggests that the non-coding RNAs of the virus contribute to viral immune escape to prevent immune eradication. This knowledge might be used in the future to attenuate EBV for vaccine development against this human tumor virus that was discovered more than 55 years ago.